The effects of organic planting medium on growth and root formation of tea seedling at early stage of tea nursery - Salwa Lubnan Dalimoenthe (Jurnal Penelitian Teh dan Kina, 2013)
Tea plants commonly propagated through vegetative propagation using single node leaf cutting and planting on mixed of topsoil and subsoil. From time to time, it is difficult to get suitable soil for nursery and the activity could disturb ecosystem. In addition, the medium weight would become a constraint in transporation of tea seedling. To overcome these problems, an alternative planting medium of tea seedling has to be explored to reduce the use of soil. In this research, various organic materials have been tested to know their effect on growth and root formation of tea seedling at early stage of tea nursery. The experiment arranged in a complete randomized design with nine treatments, replicated three times. Treatments tested were combination of organic matter (cocopith, rice husk, sawdust, and peat soil) with top soil (15% and 25%). Cow dung, as organic fertilizer, was added to enrich planting medium. Results shows that cocopith, rice husk, sawdust, and peat soil enriched with cow dung resulted the same with top soil medium (convensional planting medium) on growth and root formation of tea seedlings at early stage of tea nursery.